Vibrating nanoneedle and lab-on-chip microfluidics system for single cell mechanics - Rahman, Md. Habibur (2015)
Single cell mechanics is a vital part of single cell analysis. It has attracted great interest among scientists as cell mechanics can be linked to early diagnosis of diseases. To date, several great findings have been achieved in the study of single cell mechanics. Nevertheless, more work are required to enable the technology to be pushed to the frontier of single cell mechanics. Considering this objective, this work focuses on the technological development of two major parameters of single cell mechanics: Single Cell Wall (SCW) cutting operations (Phase 01) and Single Cell Mass (SCM) measurement (Phase 02). A saccharomyces cerevisiae yeast cell was used as a sample cell. In phase 01, a vibrating nanoneedle (tungsten) integrated with lead zirconate titanate piezoelectric actuator was used for SCW cutting operation. Two different frequencies of vibrating nanoneedle were used for cell wall cutting operation: 1 Hz and 10 Hz. For a constant penetration depth of 1.2 µm, the obtained cell nanoneedle’s velocities were 7 µm/s and 24 µm/s. Results show that faster nanoneedle causes less damage to the cell surface. In phase 02, a Lab-On-Chip microfluidics system was used for SCM measurement. SCM result was extracted from the relation between drag force applied on cell and Newton’s law of motion. Drag force on the cell has been generated by a pressure driven syringe micropump. This approach of measuring SCM was calibrated using a known mass (73.5 pico gram) of polystyrene particle of 5.2 µm diameter. Different sizes (2-7 µm diameter) of yeast cells were cultured in our laboratory. Mass of 4.4 µm diameter of yeast cell was measured as 2.12 pg. In addition, results show that single yeast cell mass increases exponentially with the increase of cell size. It is envisaged that this work i.e. combination of single cell cutting operation and single cell mass measurement system will add a significant contribution to the knowledge of cell mechanics and single cell analysis.